Half-Sandwich d6-Metal (CoIII, RhIII, IrIII, RuII)-Catalyzed Enantioselective C–H Activation - Qian, Pu-Fan; Li, Jun-Yi; Zhou, Yi-Bo; Zhou, Tao; Shi, Bing-Feng (SynOpen, 2023)
Transition-metal-catalyzed enantioselective C–H activation provides a straightforward strategy to synthesize chiral molecules from readily available sources. In this graphical review, we summarize the progress on half-sandwich d6-metal (CoIII, RhIII, IrIII, RuII)-catalyzed enantioselective C–H functionalization reactions. The review is categorized according to the type of metal catalyst and chiral ligand employed. Representative enantio-determining models and catalytic cycles are presented.
Keywords: enantioselectivity; C–H activation; half-sandwich; cobalt; rhodium; iridium; ruthenium; chiral carboxylic acid